Răspuns:
Explicație pas cu pas:
[tex]\bf \Big(2^{6n+1}+2^{3n+2}+1\Big)=[/tex]
[tex]\bf\Big(2^{6n}\cdot 2^{1}+2^{3n}\cdot2^{2}+1\Big)=[/tex]
[tex]\bf\Big(\big(2^2\big)^{3n}\cdot 2^{1}+2^{3n}\cdot2^{2}+1\Big)=[/tex]
[tex]\bf\Big[2^{3n}\cdot2^{1}\cdot\Big(2^{2}\cdot 2^{1-1}+2^{3n-3n}\cdot2^{2-1}\Big)+1\Big]= [/tex]
[tex]\bf\Big[2^{3n}\cdot2^{1}\cdot\Big(2^{2}\cdot 2^{0}+2^{0}\cdot2^{1}\Big)+1\Big]=[/tex]
[tex]\bf\Big[2^{3n+1}\cdot\Big(4+2\Big)+1\Big]=[/tex]
[tex]\bf\Big(2^{3n+1}\cdot6+1\Big)~\not\vdots~~7[/tex]
La cum este scris exercițiul nu este divizibil cu 7
Se respecta ordinea efectuării operațiilor